Kesan kepuasan pelanggan dan halangan untuk beralih terhadap kesetiaan pelanggan perkhidmatan telekomunikasi selular prabayar - Liong , Choong Yeun; Zulkhibri Ismail ,; Nur Riza Mohd. Suradi, (Penerbit ukm, 2005)
Nowadays mobile telecommunication services are expanding rapidly with the service providers competing to provide the best and the latest in products and services. In order to expand and stabilize in this competitive market, service providers should give attention to customer loyalty. Previous researches have shown that customer loyalty is contributed by customer satisfaction and switching barrier. However, those articles mainly focused on the postpaid telecommunication services. Therefore, this article is aimed at the prepaid telecommunication services because a large portion of the telecommunication users in Malaysia choose prepaid rather than postpaid services. A survey has been conducted in the Klang Valley area. Analyses have been performed in two stages, namely the exploratory and the confirmatory analyses. Further, the customer loyalty model has been created and confirmed using Structural Equation Modelling (SEM). The result indicates that customer loyalty of prepaid mobile telecommunication services in the Klang Valley has been contributed to, only by customer satisfaction. The result has provided the general indicator of the pattern of customer loyalty in the Klang Valley that can be used as a guideline in implementing activities for maintaining one’s market as well as customers